A Common Anesthesiology Procedure for a Patient with an Uncommon Combination of Diseases: A Case Report. (12th December 2012) - Tympa, Aliki; Hassiakos, Dimitrios; Salakos, Nikolaos; Melemeni, Aikaterini
Abstract : Administering neuraxial anesthesia to a patient with an underlying neurological disease and a combination of four other pathological disorders can be challenging. We report in this paper the case of a 45-year-old woman with neurological deficit due to ischemic brain infarct, multiple sclerosis, antiphospholipid syndrome, and β -heterozygous thalassemia that was subjected to abdominal hysterectomy and bilateral salpingoophorectomy under epidural anesthesia for ovarian cancer.